MiR‐193b availability is antagonized by LncRNA‐SNHG7 for FAIM2‐induced tumour progression in non‐small cell lung cancer. (12th November 2017) - She, Kelin; Yan, Hui; Huang, Jun; Zhou, Huaping; He, Jianxing
Abstract: Objectives: Long non‐coding RNAs have identified to involve into the tumour cell proliferation, apoptosis and metastasis. We previously found that up‐regulated LncRNA‐SNHG7 (SNHG7) positively correlated to the Fas apoptosis inhibitory molecule 2 (FAIM2) in lung cancer cells with unclear mechanism. Methods: Non‐small cell lung cancer (NSCLC) and relative normal tissues (n = 25) were collected. The SNHG7 expression and function in NSCLC was determined. The SNHG7‐miR 193b‐FAIM2 network was analysed in vitro and vivo. Results: We reported that oncogene SNHG7 predicted a poor clinical outcome and functioned as competitive endogenous RNA (ceRNA) antagonized microRNA‐193b (miR‐193b) to up‐regulate the FAIM2 level in NSCLC. Bioinformatic analysis predicted that SNHG7 harboured miR‐193b‐binding sites, and we found decreased miR‐193b levels in NSCLC tissues when compared to relative normal tissues. Luciferase assays indicated that overexpression of miR‐193b inhibited the Ruc expression of plasmid with miR‐193b‐binding sites of SNHG7 in a dose‐dependent manner. Ectopically expressed SNHG7 also as a molecular sponge sequestered endogenous miR‐193b. Besides, FAIM2 was found to be directly targeted by miR‐193b. The restoration of miR‐193b levels in NSCLC cell lines A549 and H125 suppressed the expression of FAIM2 and related tumour proliferation, metastasis and induced apoptosis. However, forced expression of SNHG7 could down‐regulate miR‐193b to elevate the FAIM2 level of tumour cells, leading to impaired miR‐193b/FAIM2‐induced tumour progression. Knockdown of SNHG7 in vivo significantly delayed the tumour growth with decreased tumour volume, which accompanied with enhanced miR‐193b expression and reduced FAIM2 levels. Conclusion: The results indicated that miR‐193b is indispensible for the ceRNA role of SNHG7 in FAIM2‐supported tumourigenesis of lung cancer.